Estudio y lucha: memorias del movimiento estudiantil universitario salvadoreño en el contexto neoliberal de posguerra - Henríquez Chávez, Alan Marcelo (CIICLA, Universidad de Costa Rica, 2018)
The article deals with the dissolution process of the de General Association of Salvadoran University Students (AGEUS) using as oral sources the memorials of two former militants from the 1992-2000 period. The discussion aims to understand how, in a context of new civil liberties and guarantees, an association with reported activity since 1927 is dismantled less than ten years after the Peace Agreements (1992). The document is structured in three parts: a brief description of the Association’s historic relevance, a  summarized explanation of the neoliberal adjustments of the postwar period in El Salvador, and selections from the memoirs of two former militants in the Association’s last period of activity. The conclusions allow to question the mechanisms the FMLN guerrilla used for its transition to a political party, taking leaders of the social movements and some of them without direction in the process.